Observational study of tympanic membrane changes in allergic rhinitis - Katiyar, V. M. Hemlata; Elango, D.; Prasanna, Vincent (International Journal of Research in Medical Sciences, 2016)
Background: Allergic rhinitis (AR) is a common condition affecting 20-30% of the population. This condition affects not only the nose but also the sinuses and ears in many ways. Many studies are there worldwide implicating AR as a cause of serous otitis media. But only few studies have actually studied the tympanic membrane (TM) changes observed in patients with allergic rhinitis. The aim of this study is to document the TM changes observed in patients with AR and to correlate them with the duration of symptoms and also influence of prior treatment of AR on the TM changes observed. Methods: A total of 111 patients and so 222 ears were studied. A detailed history of the duration of symptoms and any prior treatment for AR was recorded. The TM changes seen were classified and recorded. The duration of disease and treatment were taken as grouping variables and the tympanic membrane changes were ranked and used as testing variable. The results were statistically analyzed using non- parametric test, Kruskal – Wallis test. Results: There was no statistically significant correlation between duration of AR and the TM changes observed. However there was a significantly less number of patients with TM retraction observed in the patients who had taken prior treatment compared to those patients who had taken no prior treatment. Conclusions: It is concluded that institution of early treatment may prevent development of Eustachian tube dysfunction and TM changes in patients with AR.